2019
DOI: 10.1016/j.wjorl.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Management of pediatric peritonsillar and deep neck infections‐ cross‐ sectional retrospective analysis

Abstract: ObjectiveDeep neck infections (DNI) are responsible for significant morbidity in children and healthcare expenditures. Few studies exist specifically addressing the clinical and epidemiologic characterization and management of DNI's in the pediatric population. Our goal was to analyse the demographic characteristics, clinical presentation, diagnostic and therapeutic approaches of peritonsillar and DNI in pediatric patients.MethodsThe medical records of patients, aged up to 18 years, admitted for peritonsillar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
1
8
2
Order By: Relevance
“…In group I (0-18 age group) Staphylococcus aureus has the highest incidence in the summer, the lowest in the autumn (p = 0.0192). In agreement with the literature [1,2,6,23,38,39], we consider the findings regarding the seasonality of the individual microbial agents interesting from an epidemiological point of view. From a clinical point of view, the treatment strategy remains the same.…”
Section: The Spectrum Of Microbial Agents Based On Gender Age and Sesupporting
confidence: 91%
See 1 more Smart Citation
“…In group I (0-18 age group) Staphylococcus aureus has the highest incidence in the summer, the lowest in the autumn (p = 0.0192). In agreement with the literature [1,2,6,23,38,39], we consider the findings regarding the seasonality of the individual microbial agents interesting from an epidemiological point of view. From a clinical point of view, the treatment strategy remains the same.…”
Section: The Spectrum Of Microbial Agents Based On Gender Age and Sesupporting
confidence: 91%
“…Differences in the PTA incidence in individual periods of the year (spring, summer, autumn, and winter) are not significant in our group (p = 0.4396), nor were they significant in studies from Denmark, England, or the USA [13,23,37]. Other studies have reported significant differences in the seasonal incidence of PTA in a group of pediatric patients with the highest incidence in the spring or summer [6,38,39]. In our work, a detailed analysis revealed that the incidence of PTA in boys in group I (0-18 years) is statistically significantly higher during the summer and, conversely, is at its lowest in the autumn (p = 0.0023).…”
Section: The Spectrum Of Microbial Agents Based On Gender Age and Secontrasting
confidence: 71%
“…The antibiotic regimens were different from each other in all eight cases with this information provided. In addition to the twelve well-described cases, Hsiao et al and Menezes et al each reported a case of upper airway obstruction among 56 and 71 children with PTA, respectively [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, once PTA progresses to DNI and mediastinitis, the mortality rate will increase substantially [31]. According to the literature, approximately 2% of PTA may be complicated by DNI, but few studies have explored whether comorbidities increase the chance of the PTA-DNI complication [32]. In our study, PTA was complicated with DNI in 4.2% of the hemodialysis patients-higher than the previously reported prevalence.…”
Section: Discussionmentioning
confidence: 49%